Copper delivery to an endospore coat protein of Bacillus subtilis - Lee, Jaeick; Dalton, Rosemary A.; Dennison, Christopher (Frontiers in Cell and Developmental Biology, 2022)
A family of cytosolic copper (Cu) storage proteins (the Csps) bind large quantities of Cu(I) via their Cys-lined four-helix bundles, and the majority are cytosolic (Csp3s). The presence of Csp3s in many bacteria appears inconsistent with the current dogma that bacteria, unlike eukaryotes, have evolved not to maintain intracellular pools of Cu due to its potential toxicity. Sporulation in Bacillus subtilis has been used to investigate if a Csp3 binds Cu(I) in the cytosol for a target enzyme. The activity of the Cu-requiring endospore multi-Cu oxidase BsCotA (a laccase) increases under Cu-replete conditions in wild type B. subtilis. In the strain lacking BsCsp3 lower BsCotA activity is observed and is unaffected by Cu levels. BsCsp3 loaded with Cu(I) readily activates apo-BsCotA in vitro. Experiments with a high affinity Cu(I) chelator demonstrate that Cu(I) transfer from Cu(I)-BsCsp3 must occur via an associative mechanism. BsCsp3 and BsCotA are both upregulated during late sporulation. We hypothesise that BsCsp3 acquires cuprous ions in the cytosol of B. subtilis for BsCotA.